Effect of the Group Music Therapy on Brain Wave, Behavior, and Cognitive Function among Patients with Chronic Schizophrenia - Myoungjin Kwon, RN, PhD; Moonhee Gang, RN, PhD; Kyongok Oh, RN, PhD (Elsevier, 2013)
Purpose: The purpose of the study was to examine the effect of group music therapy on brain waves, behavior, and cognitive function among patients with chronic schizophrenia. Methods: A quasi-experimental pretest-posttest design was used with nonequivalent control group. The potential participants were recruited from inpatients in a psychiatric facility in a metropolitan city, assigned either to the experimental group (n = 28) or to the control group (n = 27) according to their wards to avoid treatment contamination. The experimental group participated in the group music therapy for 13 sessions over 7 weeks while continuing their standard treatment. The control group only received a standard treatment provided in the hospitals. The outcome measures include brain wave by electroencephalography, behavior by Nurses' Observation Scale for Inpatient Evaluation, and cognitive function by Mini-Mental State Examination. Results: After participating in 13 sessions of the group music therapy, alpha waves measured from eight different sites were consistently present for the experimental group (p = .006-.045) than the control group, revealing that the participants in the music therapy may have experienced more joyful emotions throughout the sessions. The experimental group also showed improved cognitive function (F = 13.46, p = .001) and positive behavior (social competence, social interest & personal neatness) while their negative behaviors was significantly less than those of the control group (F = 24.04, p < .001). Conclusion: The group music therapy used in this study was an effective intervention for improving emotional relaxation, cognitive processing abilities along with positive behavioral changes in patients with chronic schizophrenia. Our results can be useful for establishing intervention strategies toward psychiatric rehabilitation for those who suffer from chronic mental illnesses.